Optimization of Drilling Cutting Parameter and Analysis of Chip Formation When Producing Hole for S50C Material - Abd Aziz, Abdul Hafiz; Rafai, Noor Hakim (Research Progress in Mechanical and Manufacturing Engineering, 2021)
The geometry of the cutting tool and the cutting parameters strongly influence the shape and forming mechanism of the chip in the final drilling process. Therefore, the objective of this study is to optimize the cutting parameters of the drilling process in terms of cutting speed and feed rate by using surface roughness as the response. On the other hand, this study is to compare the performance of two types of cutting tools with different geometry designs (DRS and EZ) in terms of chip formation, chip thickness, and chip width. Chip formation, chip thickness, and chip width were observed and measured by using a tool maker microscope while surface roughness was measured by surface roughness tester. The result shows a strong relationship between cutting parameters especially cutting speed and feed rate in the chip formation analysis. Besides, the increase of feed rate provides an opportunity to decrease the chip thickness and chip width for both different geometry designs of the cutting tool. Moreover, chip thickness and chip width are more affected by the feed rate. For surface roughness, the DRS drilling bit is most affected by cutting speed and for the EZ drilling bit, it is affected by feed rate. In conclusion, the best drill bit to be used in this experiment is the EZ type where it has a standard flute with a curve design on its cutting lips. EZ drill produced a low value of surface roughness (low than 1.5 μm) where the lowest value is 0.821 μm.